ICT Solutions for Energy Efficiency - Youngman, Richard (World Bank, Washington, DC, 2013)
The report is focused on showing a wide range and variety of ways in which Information and Communication Technologies (ICT) solutions could play a transformative role, and so the bulk of the report provides case studies of actual examples of ICT solutions already developed and in action to enable energy efficiency in three particular areas, namely, smart logistics, smart grid/smart metering, and smart buildings. Ultimately, in line with the WBG's charter, this study is concerned with the question of how ICT can play a transformative role in developing countries'climate-smart future. However, as the World Development Report 2010 recognized, this is bound to start in higher-income countries, which have the incentives (being high-energy and high-cost users), the technical know-how and the resources to innovate and implement pioneering solutions to cut their costs and their carbon emissions. Some such solutions will have applicability to the developing world; a minority right away, more year by year as technology is proven and efficiencies of scale kick in. The report concludes with some thoughts, drawn out of these case studies, on the trajectory of ICT in energy efficiency in the world generally, but especially within the focus areas of logistics, the grid and buildings, and on what these case studies might mean for developing countries and their priorities in terms of energy efficiency.